THE STUDY ON MOBILE BANKING APPLICATION USE: THE PERSPECTIVE OF TAM, PERCEIVED RISK, AND TRUST - Rabbani, Giovanni Muhammad Sulthon (Jurnal Ilmiah Mahasiswa FEB, 2021)
This study aimed to explain the factors influencing consumers to use M-Banking as a service provided by banks to carry out various banking transactions to their users based on the Technology Acceptance Model (TAM) theory. The research data were analyzed using a structural equation model (SEM) based on Partial Least Squares (PLS). Data were collected using a survey method, namely, a questionnaire. Respondents were 301 active undergraduate students from the Faculty of Economics and Business, Universitas Brawijaya. The data analysis technique used path analysis. The study results indicate that there is an influence from the perspective of use (perceived usefulness), perspective of ease of use (perceived ease of use), direct trust (perceived risk), and significant impact on behavioral intention (behavioral intention). The perceived risk is direct and insignificant towards Behavioral Intention. The analysis results show that perceived risk and behavioral intention directly and do not significantly influence using M-Banking.Keywords: Behavioral Intentions, TAM, Perceived Risk, and Trust